Studies in the islam and science nexus - Iqbal, Muzaffar ([S.l.] : Ashgate, 2012)
This four volume series brings together the most important and influential articles dealing with various aspects of the relationship between Islam and science. The studies reflect historical, epistemological and philosophical issues and perspectives, and cover a wide spectrum of subject areas ranging from Islamic perspectives on cosmology and biological evolution to the relationship between the Qur'an and science, and contemporary issues in many fields where science and religion interact. The series sheds new light on historical links between modern science and the Islamic scientific tradition and also includes special studies on major voices in Islam and science discourse. Each volume in the series is thematically arranged, which makes clear the developments in various sub areas of the Islam and science nexus, and includes an introduction which presents an overview of the current status of research in the field. This series constitutes a comprehensive reference resource for libraries and academic researchers interested in all aspects of the Islam and science discourse.